The role of mindfulness and decentering in depressive and anxious symptoms - Leticia Linares; Ana Estévez; Joaquim Soler; Ausiàs Cebolla (Clínica y Salud. Investigación Empírica en Psicología, 2016)
Depressive and anxious symptoms have a clear impact on the functioning of people. Their appearance seems to be related to the presence of deficits in metacognitive capacities. Mindfulness interventions increase metacognitive awareness through their effect in the decentering capacity. Therefore, the aim of this study was to evaluate the relationship between mindfulness and decentering with anxious and depressive symptomatology respectively. The sample consisted of 465 participants contacted through universities and social networks. Results revealed that both mindfulness and the ability to decenter explain the presence of depressive symptoms while only mindfulness explains the presence of anxiety symptoms. These results are encouraging for intervention in mindfulness with anxious and depressive symptoms and stress the importance of metacognitive processes such as decentering in their development.